Measurement of leading neutron production in deep-inelastic scattering at HERA - Aaron, Francisc Dionisie; Radescu, Voica; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2010)
The production of leading neutrons, where the neutron carries a large fraction xLof the incoming proton’s longitudinal momentum, is studied in deep-inelastic positron-proton scattering at HERA. The data were taken with the H1 detector in the years 2006 and 2007 and correspond to an integrated luminosity of 122 pb−1. The semi-inclusive cross section is measured in the phase space defined by the photon virtuality 6<Q2<100 GeV2, Bjorken scaling variable 1.5⋅10−4<x<3⋅10−2, longitudinal momentum fraction 0.32<xL<0.95 and neutron transverse momentum pT<0.2 GeV. The leading neutron structure function, $F_{2}^{LN(3)}(Q^{2},x,x_{L})$, and the fraction of deep-inelastic scattering events containing a leading neutron are studied as a function of Q2, x and xL. Assuming that the pion exchange mechanism dominates leading neutron production, the data provide constraints on the shape of the pion structure function.
*The H1 Collaboration: F.D. Aaron, V. Radescu, M. Sauter, A. Schöning, H.-C. Schultz-Coulon [und 230 weitere Personen]
Gesehen am 15.11.2022